Oligonucleotides with rapid turnover of the phosphate groups occur endogenously in eukaryotic cells. - Plesner, P (1987)
Endogenous oligonucleotides were found in trichloroacetic acid extracts of hamster lung fibroblasts and Tetrahymena cells. Peaks of radioactivity that eluted with retention times similar to oligonucleotide markers (5- to 50-mer) were found by HPLC in cells labeled briefly with 32Pi. Only minute amounts of UV-absorbing material were detected, consistent with a rapid turnover of phosphate groups. The 32P-labeled material also migrated as oligonucleotides on 20% polyacrylamide gels; it was not hydrolyzed by alkaline phosphatase but was digested by snake venom phosphodiesterase, S1 nuclease, and pancreatic RNase and was phosphorylated by T4 polynucleotide kinase. The 32P-labeled material isolated by HPLC was alkali labile and the hydrolyzate ran as nucleotides on paper chromatography. It is concluded that the oligonucleotides are mainly oligoribonucleotides, but it is possible that oligodeoxynucleotides are also present.